Cilostazol inhibits interleukin‐1‐induced ADAM17 expression through cAMP independent signaling in vascular smooth muscle cells. (22nd December 2015) - Takaguri, Akira; Morimoto, Mayumi; Imai, Shin‐ichi; Satoh, Kumi
Abstract: Increased A disintegrin and metalloprotease 17 (ADAM17) expression in vascular smooth muscle cells (VSMC) is implicated in the development of cardiovascular diseases including atherosclerosis and hypertension. Although cilostazol, type III phosphodiesterase (PDE III) inhibitor, has recently been found to inhibit VSMC proliferation, the mechanisms remain largely unclear. Here, we hypothesized that cilostazol regulates the ADAM17 expression in VSMC. In cultured VSMC, interleukin (IL)‐1α and IL‐1β significantly increased ADAM17 expression. MEK inhibitor U0126, NF‐κB inhibitor BAY‐11‐7085, and siRNA targeting p65/RelA significantly inhibited IL‐1α or IL‐β‐induced ADAM17 expression. Cilostazol significantly inhibited IL‐1α or IL‐1β‐induced extracellular signal‐regulated kinase (ERK) phosphorylation and ADAM17 expression. Unexpectedly, cilostamide, dibutryl cAMP, and forskolin did not affect IL‐1‐induced ADAM17 expression. Our results clearly demonstrated that IL‐1 induces ADAM17 expression through ERK/NF‐κB activation in VSMCs. Moreover, the inhibitory effects of cilostazol on IL‐1‐induced ADAM17 expression may be independent of the cAMP signaling pathway in VSMC. These novel findings may provide important clues to understanding the expression mechanisms of ADAM17 and the inhibitory mechanisms of cilostazol in VSMC proliferation.